2015
DOI: 10.1007/s40273-015-0334-3
|View full text |Cite
|
Sign up to set email alerts
|

Vedolizumab for the Treatment of Adults with Moderate-to-Severe Active Ulcerative Colitis: An Evidence Review Group Perspective of a NICE Single Technology Appraisal

Abstract: As part of its single technology appraisal (STA) process, the National Institute for Health and Care Excellence (NICE) invited the manufacturer of vedolizumab (Takeda UK) to submit evidence of the clinical effectiveness and cost-effectiveness of vedolizumab for the treatment of patients with moderate-to-severe active ulcerative colitis (UC). The Evidence Review Group (ERG) produced a critical review of the evidence for the clinical effectiveness and cost-effectiveness of the technology, based upon the company'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(50 citation statements)
references
References 24 publications
(53 reference statements)
1
49
0
Order By: Relevance
“…Second, previous cost-effectiveness analyses have characterized disease severity during the maintenance phase using three health states, defined by patients' Mayo score: remission (Mayo score 0-2), mild UC (Mayo score 3-5), and moderate-to-severe UC (Mayo score 6-12) [17,18,60]. This approach has been criticized by an independent Evidence Review Group (ERG) during a NICE single technology appraisal of VDZ for the treatment of patients with moderate-to-severe UC in the UK, as this approach ignored that patients in the mild and moderate-to-severe UC health states can include both patients with and without response [61]. The ERG suggested that this issue could have been addressed by modeling the maintenance phase transitions between moderate-to-severe UC, response, and remission health states, using the patient-level data from the GEMINI I clinical trial [15,61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, previous cost-effectiveness analyses have characterized disease severity during the maintenance phase using three health states, defined by patients' Mayo score: remission (Mayo score 0-2), mild UC (Mayo score 3-5), and moderate-to-severe UC (Mayo score 6-12) [17,18,60]. This approach has been criticized by an independent Evidence Review Group (ERG) during a NICE single technology appraisal of VDZ for the treatment of patients with moderate-to-severe UC in the UK, as this approach ignored that patients in the mild and moderate-to-severe UC health states can include both patients with and without response [61]. The ERG suggested that this issue could have been addressed by modeling the maintenance phase transitions between moderate-to-severe UC, response, and remission health states, using the patient-level data from the GEMINI I clinical trial [15,61].…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been criticized by an independent Evidence Review Group (ERG) during a NICE single technology appraisal of VDZ for the treatment of patients with moderate-to-severe UC in the UK, as this approach ignored that patients in the mild and moderate-to-severe UC health states can include both patients with and without response [61]. The ERG suggested that this issue could have been addressed by modeling the maintenance phase transitions between moderate-to-severe UC, response, and remission health states, using the patient-level data from the GEMINI I clinical trial [15,61]. We followed the ERG's recommendation, and the model structure is in line with previous models [62].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have performed network meta‐analyses assessing the efficacy of various anti‐tumor necrosis factor (TNF)‐α agents for the treatment of UC . Essat et al found eight studies among four anti‐TNF‐α agents and have shown that infliximab was superior to other agents for clinical response, remission, and mucosal healing among anti‐TNF‐α naive patients in the induction phase . Thorlund et al and Stidham et al found comparable efficacy between three anti‐TNF‐α agents .…”
Section: Discussionmentioning
confidence: 99%
“…36,38 Essat et al found eight studies among four anti-TNF-α agents and have shown that infliximab was superior to other agents for clinical response, remission, and mucosal healing among anti-TNF-α naive patients in the induction phase. 36 Thorlund et al and Stidham et al found comparable efficacy between three anti-TNF-α agents. 37,38 These studies did not include any loop in the network and lacked assessment of the inconsistency factor making it difficult to interpret the strength of evidence.…”
Section: Discussionmentioning
confidence: 99%
“…209 210 Although nasopharyngitis and arthritis have been reported as side effects of vedolizumab, 211 212 extensive clinical experience over the past eight years has amply validated the safety and effectiveness of vedolizumab for the induction and maintenance of remission in patients with Crohn's disease and ulcerative colitis. [213][214][215][216][217][218] Progressive multifocal leukoencephalopathy has not been reported with vedolizumab and JC virus does not need to be checked before starting treatment. 219 Whenever a new agent shows efficacy and safety, the question arises whether to use it as the primary biologic treatment, to reserve it for rescue when anti-TNF therapy is ineffective, or to introduce it for maintenance of remission induced by another drug that is too toxic to use long term (for example, steroids, ciclosporin).…”
Section: Anti-attractantsmentioning
confidence: 99%